Determinant Analysis of Work Motivation and Its Impact on Employee Performance at Halu Oleo Kendari University - Muhammad Amir; Harries Madiistriyatno; BB Suriyani; Rahman Rahman; Sitti Hairani Idrus (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This look at ambitions to take a look at the effect of duty, organizational culture and management ethics on worker paintings motivation and on employee overall performance at Halu Oleo-Kendari University. This studies uses a correlation test approach this is useful for explaining whether there may be a relationship between variables. In In this study, the sample consisted of 30 workforce individuals at the Faculty of Social and Political Sciences. Respondents have been decided on using a random sampling technique. Correlation take a look at with a couple of regression evaluation method is used to check the speculation. Before us checking out the hypotheses, element evaluation and classical assumption assessments were accomplished to check the validity and reliability of the instrument and the fine of the information. The studies results show that organizational subculture and ethical management has a effective effect on the work motivation of the staff individuals of the Faculty of Social and Political Sciences and their overall performance. Whereas responsibility only undoubtedly affects performance and now not on worker motivation on the Faculty of Social and Political Sciences.